THE TENDENCY TOWARDS CENTRALIZATION EXPERIENCED IN THE MANAGEMENT OF METROPOLITAN MUNICIPALITIES IN TURKEY - Orhan Veli Alıcı (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Compared to the past, the subsidiarity principle has become more apparent with the implementation of the Metropolitan Municipality Law No. 5216 in 2004 and the Municipality Law No. 5393 in 2005. While the metropolitan municipalities were empowered with the development called the reform of local governments, the duties and authorities of the district municipalities in metropolitan cities were reduced. Due to the administrative power of the district municipalities, metropolitan municipalities almost became “new centers” at the local level. In case, the discourse of localization actually caused a new centralization movement in the local administration system of Turkey. Moreover, with the abolition of special provincial administrations, the duties and authorities of metropolitan municipalities expanded to rural areas. Therefore, the centralization process in local governments contained all of the city boundaries. In this article, the centralization tendency in the case of metropolitan municipalities that makes them “leaders of local governments” in metropolitan cities where a two-level metropolitan management system is applied will be examined.